COMPARATIVE PERFORMANCE OF THE VISEGRAD GROUP BANKS FOR THE PERIOD 2009 -2013 - Černohorská, Liběna; Pilyavskyy, Anatoliy; Aaronson, William (My University, 2017)
The article examines the comparative performance of Banks for the Visegrad group (V4) of four Central European States for the period 2009-2013. We study the technical efficiency as well as the total factor of productivity changes differences between countries by employing the Data Envelopment Analysis. The efficiency scores are calculated with an output-oriented model. Specification of inputs and outputs is one of the major problems for measurement of bank’s efficiency and productivity changes. To determine inputs and outputs, we made use of assets approach that treats banks as classical intermediators between depositors and borrowers. We have determined three inputs (personnel, physical capital, purchased funds) and two outputs: net loans, total securities. Our results showed that average technical efficiency (for all banks) trended upward during the study period. This increase efficiency is not common for all banks in the Czech Republic, Poland, Hungary and Slovak. We found that efficiency for Czech, Polish and Slovak banks increase during research time. Development of efficiency Hungarian banks has on the contrary a downward trend from 0.882 in 2009 to 0.856 in 2013. We also founded that the Total Factor of Productivity (TFP) changes across all countries was relatively stable in 3 of the 4 observation periods. However, there was a substantial decline in TFP in 2011-12. Examination of the trends for each of the countries showed that Hungary overly influenced the sample mean. The TFP remained stable during this period for all Poland and Czech Republic, declined slightly for Slovakia, but declined precipitously for Hungary in 2011-12.
Srovnání efektivnosti bank Visegrádské skupiny v letech 2009-2013
Keywords: Performance of Banks; Visegrad Group; Technical Efficiency; Total Factor of Productivity Changes; Visegrádská skupina; technická efektivnost; výkonnost bank; celková změna produktivity